Evidence-based approaches to comparing the effectiveness of modern cardiology interventions: trends, bias and prospects - S. R. Gilyarevsky; Yu. N. Belenkov (Российский кардиологический журнал, 2020)
The article discusses the limitations of the evidence from observational studies. Modern approaches to reducing bias in observational studies are discussed in detail, in particular, propensity score matching, which has become popular in recent years. The main differences between randomized and observational studies are discussed. Arguments against the observational studies and improved methods of analysis to compare the treatments’ effectiveness in clinical practice are presented. The role of observational studies as a source of evidence is discussed. The article points out the validity of performing large-scale prospective observational studies to assess the effects of postmarketing drug use in clinical practice, as well as to obtain data on drug use in patients that differ from those in randomized clinical trials.